An analysis of social dimensions of podoconiosis and leprosy on affected households in endemic health districts of the North West Region of Cameroon. (September 2022) - Tembei, Ayok M.; Kengne-Ouafo, Jonas A.; John, Bonekeh; Nji, Theobald M.; Enyong, Peter; Nkuo-Akenji, Theresa; Davey, Gail; Wanji, Samuel
Abstract: Background: Podoconiosis and leprosy are Neglected Tropical Diseases associated with low quality of life, social stigma and isolation of affected people and families. Despite the substantial social burden it imposes, podoconiosis has largely been ignored in the global health literature until recently unlike leprosy. This study assessed and compared the quality of life and social impact of podoconiosis with that of leprosy among affected households and neighborhoods in North West Cameroon. Methods: A comparative cross-sectional design was used. Eighty-six households: 43 podoconiosis and 43 leprosy, plus household neighbours were enrolled from July and August 2015 from three health districts. Podoconiosis patients living in households within Batibo and Ndop health districts were sequentially sampled using a list of confirmed podoconioisis cases from previous studies. Leprosy patients living within communities in Mejang Health Area were sequentially sampled using the Mbingo treatment center register. WHO BREF tool was used to assess quality of life. Franklin Stigma Scale was adapted to assess felt and enacted stigma. Mann-Whitney U test was used to compare differences in stigma and QoL. Results: Physical domain showed a significant difference in the distribution in quality of life between groups (p < 0.05, median:70; U:635, r = 0.2). Overall enacted stigma revealed significant differences with p < 0.05 and r = 0.4. Overall stigma from family members (median:17, U:627 and r = 0.3) and neighbours (median:67, U:336 and r = 0.5) showed significant differences with p < 0.05 in the distribution of scores for both diseases. Sex and age showed significant associations with QoL and stigma. Conclusion: This study reveals the quality of life and stigma associated with podoconiosis on affected households to be comparable to that experienced by households with a leprosy patient. There is need for intensified preventive, management and control schemes to fight podoconiosis in Cameroon, just like leprosy. Highlights: Podoconiosis and leprosy are NTDs linked with low quality of life, stigma and isolation of affected people and families. The social consequences include difficulties in finding employment, gaining education and getting married. Podoconiosis impairs similar social burden on its victims like leprosy, yet remains neglected in Cameroon unlike leprosy. This disparity in attention may be due to lack of evidence on the social impact of Podoconiosis likened to leprosy. This paper creates scientific basis on the social effects of Podoconiosis in Cameroon to inform health policy actions.